Long-term survival among elderly after burns compared with national mean remaining life expectancy. Issue 6 (September 2021) - Firchal, Emmelie Westlund; Sjoberg, Folke; Fredrikson, Mats; Pompermaier, Laura; Elmasry, Moustafa; Steinvall, Ingrid
Highlights: The long-time survival of elderly patients after burns is shorter than that of a national control. The magnitude of life shortening is quantitatively important. The current study does not support that burn related factors account for this effect. The reason should therefore be sought in other factors, such as e.g., co-morbidity or psychosocial issues. Abstract: Introduction: As compared to younger adults, older people have a greater risk of domestic accidents, such as burns, and their prognosis is worsened by a diminished physiological ability to face a thermal trauma. The in-hospital mortality is adversely affected by old age and burn size, whereas less is known about the long-term-survival in elderly patients who survive a burn injury. The aim of this study was to investigate if elderly burn patients after discharge from a Swedish National Burn Centre have a shorter remaining life compared to the national population, by using calculated remaining Life Expectancy (rLE). Methods: In this retrospective study we included all patients who were admitted for burns to the Linköping Burn Centre during 1993–2016 and who were 60 years or older and alive, at the time of discharge. The control group was extracted from Statistics Sweden, the national statistics database, and consisted of all individuals from the Swedish population matched for each patient in the study group, by sex and age at the year of discharge. The proportion who died before reaching the rLE was compared between the study population and the control group by calculating risk ratio. Results: The study group consisted of 111 former patients and 77 of them (69%) died before reaching the rLE, with mean 4.7 years of life lost (YLL), which was 33% more than that (52%) of the control group (RR 1.33, 95% CI 1.18–1.51). Burn related factors, such as TBSA % or FTB % were not found to account for this effect. Conclusion: We found that the long-time survival of elderly patients after burns is shorter than that of a national control, the magnitude of which is quantitatively important. The current study does not support that burn related factors account for this effect and the reason should therefore be sought in other factors, such as e.g., co-morbidity or psychosocial issues.